Non-intubated laparoscopic repair of giant Morgagni’s hernia for a young man - Zhang, Miao; Wang, Heng; Liu, Dong; Pan, Xuefeng; Wu, Wenbin; Hu, Zhengqun; Zhang, Hui (Journal of Thoracic Disease; Vol 8, No 8 (August 01, 2016): Journal of Thoracic Disease, 2016)
An asymptomatic patient was admitted as his chest photograph and computed tomography scans showed a giant Morgagni’s hernia (MH). And it was repaired by laparoscopic approach under epidural anesthesia without endotracheal intubation. The hernia content of omentum was repositioned back into the abdominal cavity, and the diaphragmatic defect was repaired with composite mesh. Which indicated that non-intubated laparoscopic mesh repair via epidural anesthesia is reliable and satisfactory for MH.